Effects of thermal stresses on Pressurised Water Reactor nuclear containment vessels following a Loss of Coolant Accident with assimilated containment filtered venting system - Hartnick, Angelo (Department of Electrical Engineering, 2021)
In a nuclear power plant, the last barrier under normal and accident operations is the containment building. This is normally constructed from concrete reinforced with steel bars, which are prestressed to enhance the overall capability to withstand thermodynamic stresses like over-pressurisation and high temperatures. The failure of this final barrier will lead to the release of radioactivity to the surrounding environment. To examine the effects of thermo-hydraulic stresses on PWR containment following a LOCA, a model is proposed with simulated scenarios performed at the Koeberg Nuclear Power Station as a case study. The accidents were simulated using the Koeberg engineering simulator to obtain the output data. The scenario for the proposed model correlates the critical mass flow from a double-ended guillotine break to the containment pressure and temperature increase. Different containment filtered venting systems (CFVS) are also investigated in this study as severe accident management systems. CFVS have historically been included in boiling water reactor (BWR) designs, but following the Fukushima Daiichi nuclear accident, they are being introduced as severe accident management systems to manage the threat of containment over-pressurisation in pressurised water reactors (PWR). Finally, the rate of change in containment pressure and temperature is analysed and compared to literature, with the incorporation of a simulated filtered venting system to the PWR containment building.